2019
DOI: 10.3389/fmicb.2019.01727
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapy of Paracoccidioidomycosis Using P10-Primed Monocyte-Derived Dendritic Cells Isolated From Infected Mice

Abstract: Paracoccidioidomycosis (PCM) is an endemic mycosis in Latin American caused by the thermodimorphic fungi of the genus Paracoccidioides spp. Notably, a Th1 immune response is required to control PCM. In this context, dendritic cells (DCs) seem to be essential players in capture, processing and presentation of Paracoccidioides antigens to naïve T cells and their further activation. We have previously demonstrated that differentiated DCs from bone marrow cells, pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This was also achieved with immunocompromised mice in a disease model that simulated the most aggressive form of paracoccidioidomycosis [ 56 ]. In this study, the authors isolated and generated monocyte differentiated dendritic cells from infected mice, pulsed them with P10 and then used them in the therapy of PCM in syngeneic mice [ 57 ].…”
Section: Immune System Activation and Main Effector Mechanisms Thamentioning
confidence: 99%
“…This was also achieved with immunocompromised mice in a disease model that simulated the most aggressive form of paracoccidioidomycosis [ 56 ]. In this study, the authors isolated and generated monocyte differentiated dendritic cells from infected mice, pulsed them with P10 and then used them in the therapy of PCM in syngeneic mice [ 57 ].…”
Section: Immune System Activation and Main Effector Mechanisms Thamentioning
confidence: 99%
“…Bone marrow-derived dendritic cells (BMDCs) pulsed with P10 efficiently reduced the pulmonary fungal burdens of immunosuppressed mice previously infected with P. brasiliensis and also preserved lung tissue by decreasing cellular infiltration into the organ [56]. Further work demonstrated that P10 was able to activate and modulate both BMDCs and monocyte-derived dendritic cells (MoDCs), and MoDCs pulsed with P10 similarly protected against pulmonary infection by P. brasiliensis, which is promising as this treatment most closely mirrors what would be administered to a patient with paracoccidioidomycosis [57].…”
Section: Paracoccidioidomycosis (Pcm)mentioning
confidence: 87%
“…A significant advance in the research of a possible PCM vaccine was made using one peptide of the gp43 P. brasiliensis protein (P10), which is an adhesin and significant diagnostic antigen of this mycosis. By using different vaccine approaches, the P10 peptide was able to reduce the fungal burden and to increase cytokine production [ 59 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%